THE USE OF TEXT WITH PICTURES AS THE MEDIA IN TEACHING READING COMPREHENSION:A Quasi-Experimental Study of First Grade Students in Senior High School - Yessy Tri Noviani, - (2012)
This research entitled "The Use of Text with Pictures as the Media in Teaching Reading Comprehension" was aimed at answering the question whether the use of texts with pictures significantly improve students' reading comprehension skill. Moreover, the students' responses toward the texts with pictures were also investigated. This quasi-experimental research involved two classes of students which were assigned as experimental group (N=34) and control group (N=31). The data were collected through pre-test, post-test, questionnaire, and interview. In analyzing the data, this research employed quantitative method by comparing the mean scores of both groups in pre-test and post-test. It was intended to examine the effectiveness of texts with pictures in improving students' reading comprehension. Furthermore, the data taken from questionnaire and interview were also analyzed to find out students' responses toward text with pictures. The result of this research revealed that texts with pictures significantly improve students' reading comprehension. It was evidenced by the result of statistical computation (Independent t-test) which showed that the value of t obtained (2.188) was greater than the t crit (2.000, α=0.05, df=63). Most significantly, the students' improvement could be seen in their ability to understand the whole texts faster, and to enrich their vocabularies by looking at the pictures. Meanwhile, the result of questionnaire showed that 96.9% students agreed that the use of texts with pictures was effective in improving their reading comprehension skill. It was in line with the result of interview that showed that the texts with pictures was effective to improve students' reading comprehension and it brought a lot of benefits; it helped students get better comprehension of the whole texts, it helped students understanding difficult vocabularies, and it made the learning activities more interesting and motivating.